Globalization and application of strategic management model and theories to entrepreneurs in a turbulent economy - Cheng, Wei Hin; Md Isa, Filzah; Hoe, Chee Hee (David Publishing, 2011)
Globalization had changed the competitive landscape in which entrepreneurs used to compete. There are advantages and disadvantages of doing business globally.Globalization had also brought about many challenges to entrepreneurs in the management of their organization.The values and beliefs of managers and staff across the globe influence visions, missions of their organization.Culture, resources and business practices of countries vary widely. Entrepreneurs must deal with global issues side by side with domestic considerations.This paper looks into how the theories and model of strategic management remain useful and relevant to entrepreneurs in a globalized business world especially in a turbulent economy.